Rustsim: A Process-Oriented Simulation Framework for the Rust Language - Moreno-Herrera, F (Institute of Electrical and Electronics Engineers Inc., 2023)
We present RustSim, a library for discrete-event process-oriented simulations designed and implemented in the Rust programming language. It includes a broad set of classes to allow the user to implement simulation processes and process-oriented primitives. The flexible modular design of RustSim allows users to extend its functionality. In addition, RustSim includes mechanisms to avoid inconsistencies when applying state-changing primitives that other libraries in the language s ecosystem do not provide. We take advantage of Rust generators (coroutine equivalents) to implement process-oriented simulation primitives. Finally, the library s internal process handling structure is discussed in detail, including its implementation, how simulations are executed, and a case study with a highly detailed example of its use. © 2023 IEEE.